Micro-arc oxidation of Ti6Al4V and Ti6Al7Nb alloys for biomedical applications - UĞURLU, FAYSAL (ELSEVIER SCIENCE INC, 2011)
In the present study, the in-vitro biological responses of two competitive titanium alloys (Ti6Al4V and Ti6Al7Nb) were investigated after modifying their surfaces by the micro-arc oxidation (MAO) process conducted in a (CH3COO)(2)Ca center dot H2O and Na3PO4 containing electrolyte under identical electrical parameters and exposure time. After the process, the surfaces of the alloys were covered with a thick (approx. 10 mu m) TiO2 layer exhibiting different characteristics. The oxide layer of the Ti6Al4V alloy was porous and contained hydroxyapatite precipitates whereas the oxide layer of the Ti6Al7Nb alloy showed a more grainy appearance and contained calcium titanate precipitates. Simulated body fluid (SBF) and cell culture tests were conducted to compare the biological performance of the alloys. Even though oxidized alloys exhibited somewhat similar response in SBF tests, the number of SAOS-2 cells attached to the oxide layer of the Ti6Al4V alloy was greater than that of the Ti6Al7Nb alloy. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Micro-arc oxidation; Titanium; Ti6Al4V; Ti6Al7Nb; Biocompatibility; CALCIUM-PHOSPHATE COATINGS; TITANIUM-ALLOYS; BIOACTIVITY; FILMS; CELLS; CA